Quality of Root Canal Obturation Performed by Senior Undergraduate Dental Students - Sundahnath Nagaraja (Intelektual Pustaka Media Utama, 2015)
The aim of the present study was to assess the quality of canal obturation performed by undergraduate denal students at Saveetha Dental College and Hospitals, Chennai. Records of 200 endodontically treated teeth from patients who were visited by undergraduate students between month of November 2014 to May 2015. Periapical radiographs of all treated teeth were assessed in terms of canal obturation quality (adequate density and length). Forty-five percent of teeth fulfilled the criteria of an acceptable root canal obturation. Adequate length and density of root filling was found in 89% and 34% of teeth, respectively. There was a significant difference between maxillary and mandibular teeth regarding the length of root canal obturation. A significant difference was observed between molars and other tooth types. The frequency of root canals with an acceptable filling was significantly greater in the anterior teeth compared to premolars or molars. The technical quality of root canal treatment performed by undergraduate dental students was found to be less than ideal.